Sin 2(3) is interpreted as Sin (2 * 3) = Sin 6 not as (Sin 2) * 3 so I respectfully disagree. Logically if ab is algebraically interpreted as (ab), {that is as the single number which is the product of a and b}, then a(-b) has to be interpreted as (a(-b)) = (-ab) which means that a(b) is as much of a monomial as ab is and therefore 2(3) is a monomial (a number is a monomial: the monomial 2X**0 = 2(1) = 2).

Sin 2(3) is interpreted as Sin (2 * 3) = Sin 6 not as (Sin 2) * 3 so I respectfully disagree. Logically if ab is algebraically interpreted as (ab), {that is as the single number which is the product of a and b}, then a(-b) has to be interpreted as (a(-b)) = (-ab) which means that a(b) is as much of a monomial as ab is and therefore 2(3) is a monomial (a number is a monomial: the monomial 2X**0 = 2(1) = 2).